Prevalence study of common environmental allergens in children with asthma and allergic rhinitis in Kolkata: A hospital-based study - Dey, Sanjukta; Chakraborty, Tania (Indian Journal of Child Health, 2016)
Background: Studies evaluating the role of skin prick testing (SPT) as the sole testing technique in children below 12 years of age involving a broader and more relevant group of aero- and food-allergens in this part of India are still lacking. Objectives: To identify the commonly prevalent environmental allergens by SPT in children with asthma as per British Thoracic Society and Scottish Intercollegiate Guidelines Network Criteria and allergic rhinitis (AR) as per British Society for Allergy and Clinical Immunology Criteria attending the OPD of a tertiary care pediatric unit in the eastern part of India. Methods: Testing of inhalant and food allergens by SPT in children from 4 to 12 years age group with asthma and AR satisfying the inclusion criteria. Results: Total 106 children (70 males and 36 females) were included in the study. Study of inhalant allergens in asthmatic patients revealed the highest positivity for house dust mite followed by male cockroach and among food allergens, highest positivity for egg/egg products, followed by milk/milk products. Study of inhalant allergens in asthmatic patients with coexistent AR revealed the highest positivity for house dust mite, cockroach male and female and among food allergens, highest for milk/milk products, egg/egg products, banana, and mustard. Conclusions: In Kolkata, in the eastern part of the country, among the asthmatic children of 4-12 years age group, the most common inhalant allergens were house dust mite and cockroach, whereas the common food allergens identified were milk and milk products, egg and egg products, and mustard.